An Analysis of Interpersonal Meaning in Coldplay’s Song ‘Fix You’ through Systemic Functional Linguistics - Amalia, Luqyana; Ramadhani, Tatsbita; Dewi, Intan Mustika; Rosiana, Rosiana (Universitas Stikubank (UNISBANK) Semarang, 2026)
Music lyrics frequently convey social meaning and emotional depth. The emotional sentiments in Coldplay's song